Sosialisasi Aplikasi Pupuk Nanomagnetik Pasir Besi Pada Tanaman Jagung di Desa Pulau Semambu Ogan Ilir Sumatera Selatan Sebagai Integrasi Penelitian dan Perkuliahan - Fitri Suryani Arsyad; Dedi Setiabudidaya; Menik Ariani; Idha Royani; Amiruddin Supu; Risfidian Mohadi; Aldes Lesbani; Rakhmawati Farma; Balada Soerya; Siti Nur’aini; Beta Riana Liasari (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2024)
Socialization activities have been carried out regarding the application of iron sand nanomagnetic fertilizer (Fe3O4) on corn plants to the villagers of Pulau Semambu Ogan Ilir, South Sumatra. This community service activity is part of the integration of the research results that have been carried out. From the results of the study, it was found that at the same growing age, corn added with nano-magnetic iron sand, both simaxx + nanomagnetic iron sand and silica + nanomagnetic iron sand, had a faster growth of about 100 cm compared to corn that was only given simaxx fertilizer. which is about 45-50 cm. Research results and observational data were then collected and analyzed to evaluate the effectiveness of using Fe3O4 nanomagnetic fertilizer on corn plants. Apart from being disseminated to corn farmers, research results are also used as teaching material to be conveyed to students in material physics courses. Integrating research results with community service activities and material physics lectures has increased the practical use of research results and provided wider benefits for society and students.